“The not so pretty Pearl in an Oyster” – A Case report of Primary Gastric squamous cell carcinoma with brief Literature Review - Manohar, Srijanaki; Jayakumar, Niveditha (Indian Journal of Case Reports, 2026)
Primary gastric squamous cell carcinoma (PGSCC) is an extremely rare histological subtype of gastric carcinomawith an incidence of 0.04–0.07% of all gastric cancers. It has a male preponderance and is common between 55and 80 years of age. Here, we present the occurrence of this rare tumor in a 33-year-old male, a chronic smoker andalcoholic. Imaging revealed a large heterogeneously enhancing mass in the body of the stomach. The patient underwenttotal gastrectomy with perigastric lymph node dissection. Histopathological examination of the tumor proved to be asquamous cell carcinoma with positivity for CK5/6, P63, and p16 and negative for CK7 and CK20. The tumor wasstaged pT2N0. Whole-body positron emission tomography computed tomography failed to identify an alternativeprimary squamous malignancy. PGSCC is a rare gastric malignancy that poses significant diagnostic and therapeuticchallenges. The present case is notable for its occurrence in a relatively young patient and for diffuse p16 expression,which raises the possibility of human papillomavirus-related pathogenesis. Increased reporting of such cases mayimprove the understanding of the clinicopathological features and pathogenesis of this uncommon entity